If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4x-3)-10x=-19
We move all terms to the left:
3(4x-3)-10x-(-19)=0
We add all the numbers together, and all the variables
-10x+3(4x-3)+19=0
We multiply parentheses
-10x+12x-9+19=0
We add all the numbers together, and all the variables
2x+10=0
We move all terms containing x to the left, all other terms to the right
2x=-10
x=-10/2
x=-5
| -13.8d-5.9d+10.84=18.36-18.9d | | n2-81=0 | | -16.8t+17.4=-18.5t-16.6 | | 2x=8^3 | | 5(×+y)=100 | | 3t^+24t+6=7t+5 | | 3m+10=m+4 | | -13-2w=-w | | -14q+20=-16q-20+2 | | 2p=1=5 | | 5(2m-6=12 | | -13.4r+8.47=-14.1r | | 13x-8+2x-3=12x-4+2x | | 8x+5-2x+6=15 | | 7x-3=3×+17 | | -18j-19=20-5j | | 3m=5m-8/5. | | -20u+18=-19u | | (9x+2)=(120-9x)-54 | | 3x-23=127 | | 18+10w=-2+11w | | /2m+1÷4-3m+1÷3=2÷3-m | | 17.74-3.1y=-1.5y+5.94-2.6y | | 17x=-82 | | 3(1/3+c)=7/4 | | 7x-3=3(x-4) | | x/150=40 | | 5x=7=70 | | -2-9p=-19p+7p-17 | | x/1.5=40 | | 144=(x-2)^2 | | -4-17f=-16f+9 |